The effect of Аcinetobacter calcoaceticus IMV B-7241 surfactantas on microbial adhesion to abiotic surfaces - Savenko, Inga; Pirog, Tatiana; Skrotska, Oksana (My University, 2014)
We have studied the effect of surface-active substances (SAS, surfactants) of Acinetobacter calcoaceticus IMV B-7241 with various degree of purification (the supernatant of culture liquid, the solution of SAS, 0,001-0,036 mg/ml) for the attachment of bacteria and fungi to abiotic surfaces. The degree of adhesion of the test-cultures depended on the material’s type and the concentration of SAS in the preparations. The preparation 1 (supernatant) with the concentration of SAS 0,005-0,009 mg/ml was the more effective: after treatment of the abiotic materials with this preparation the number of attached cells of bacteria and fungi decreased on average 45-60 %.
Keywords: adhesion; surfactants; abiotic materials; суфрактант; адгезія; поверхнево-активні речовини; абіотичні матеріали; кафедра біотехнології і мікробіології